Underexplored and growing economic costs of invasive alien trees - Fernandez, Romina D; Haubrock, Phillip J; Cuthbert, Ross N; Heringer, Gustavo; Kourantidou, Melina; Hudgins, Emma J; Angulo, Elena; Diagne, Christophe A; Courchamp, Franck; Nuñez, Martin A (Scientific reports, 2023)
The high ecological impacts of many invasive alien trees have been well documented. However, to date, we lacked synthesis of their economic impacts, hampering management actions. Here, we summarize the cost records of invasive trees to (I) identify invasive trees with cost information and their geographic locations, (II) investigate the types of costs recorded and sectors impacted by invasive trees and (III) analyze the relationships between categories of uses of invasive trees and the invasion costs attributed to these uses. We found reliable cost records only for 72 invasive trees, accumulating a reported total cost of $19.2 billion between 1960 and 2020. Agriculture was the sector with the highest cost records due to invasive trees. Most costs were incurred as resource damages and losses ($3.5 billion). Close attention to the ornamental sector is important for reducing the economic impact of invasive trees, since most invasive trees with cost records were introduced for that use. Despite massive reported costs of invasive trees, there remain large knowledge gaps on most invasive trees, sectors, and geographic scales, indicating that the real cost is severely underestimated. This highlights the need for further concerted and widely-distributed research efforts regarding the economic impact of invasive trees.
Keywords: Environment; zemědělství; stromy; Agriculture; Trees; zavlečené druhy; životní prostředí; Introduced Species